2021
DOI: 10.17944/mkutfd.941102
|View full text |Cite
|
Sign up to set email alerts
|

Yoğun Bakım Ünitelerinden İzole Edilen Acinetobacter Baumannıı Suşlarının Direnç Profili: Beş Yıllık Çalışma

Abstract: Amaç: Antibiyotik direnci son yıllarda tüm dünyada artış göstermiştir. Bu durum özellikle yoğun bakım ünitelerinde (YBÜ) yatan hastalarda ciddi sağlık problemi oluşturmaktadır. Acinetobacter baumannii YBÜ’de yatan hastalarda çoklu ilaç dirençli enfeksiyonların önemli bir nedeni haline gelmiştir. Bu çalışmanın amacı YBÜ’den izole edilen A.baumannii suşlarının direnç oranlarını saptamaktır. Gereç ve Yöntem:2015-2019 yılları arasında YBÜ’lerden mikrobiyoloji laboratuvarına gönderilen çeşitli örneklerden izo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…In studies from Turkey, resistance rates in ciprofloxacin were reported to be 96.1-98.8%, second only to carbapenems. [10,18] In our study, it exceeded carbapenems by 99.1%. Tigecycline is another antibiotic frequently used in Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“…In studies from Turkey, resistance rates in ciprofloxacin were reported to be 96.1-98.8%, second only to carbapenems. [10,18] In our study, it exceeded carbapenems by 99.1%. Tigecycline is another antibiotic frequently used in Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 46%
“…In the studies reported from Turkey in the past 10 years, it has been reported that resistance to carbapenems develops between 90 and 100%. [18][19][20] In our study, imipenem resistance was an average of 96.8%, and meropenem resistance was 94.2%. The widespread use of carbapenems in various infections in our ICU may cause very high resistance rates.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations